ATRT-36. META-ANALYSIS OF TREATMENT MODALITIES IN METASTATIC ATYPICAL TERATOID/RHABDOID TUMORS IN CHILDREN. Issue 2 (22nd June 2018) - Underiner, Reena; Eltobgy, Mostafa; Stanek, Joseph; Michaud, Jean; Zaky, Wafik; Bouffet, Eric; Finlay, Jonathan; AbdelBaki, Mohamed
Abstract: OBJECTIVES: Metastatic central nervous system (CNS) atypical teratoid/rhabdoid tumors (AT/RT) in children represent around 20% of newly-diagnosed AT/RT cases, and are associated with dismal prognosis. We investigated the efficacy of different treatment modalities associated with best outcomes in the management of metastatic AT/RT. METHODS: A comprehensive analysis of 2, 122 peer-reviewed manuscripts revealed 45 studies with a total of 132 metastatic AT/RT patients. Additionally, 8 patients were included from chart review performed at Nationwide Children's Hospital. RESULTS: The 3-year overall survival (OS) was 26% (95% confidence interval (CI): 18–34%). Age at diagnosis significantly impacted the OS (p=0.0225); the 3-year OS for patients <18 months was 21%, compared to 28% for patients 18–36 months and 33% for patients >36 months. Gross total resection of the primary tumor was not associated with significant improvement in the OS (p = 0.866). On univariate analysis, radiation therapy (RT), intrathecal chemotherapy (IT), and marrow-ablative chemotherapy followed by autologous hematopoietic progenitor cell rescue (AuHPCR) had a significant impact on OS, respectively (p<0.0001, p<0.05, p<0.0001). These results were further supported by multivariable analysis, in which RT (p<0.0001), IT (p=0.0227), and AuHPCR (p<0.0001) were all independently associated with reduced risk of death. CONCLUSIONS: Multimodal treatment approach should be incorporated in the management of metastatic AT/RT in children, and may include AuHPCR with adjuvant RT and IT. Given the rarity of published research focused on metastatic AT/RT, these conclusions may be an important step towards the creation of standard treatment guidelines for metastatic AT/RT patients.